2018
DOI: 10.1101/502385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anesthesia-induced loss of consciousness disrupts auditory responses beyond primary cortex

Abstract: AbstractDespite its ubiquitous use in medicine, and extensive knowledge of its molecular and cellular effects, how anesthesia induces loss of consciousness (LOC) and affects sensory processing remains poorly understood. Specifically, it is unclear whether anesthesia primarily disrupts thalamocortical relay or intercortical signaling. Here we recorded intracranial EEG (iEEG), local field potentials (LFPs), and single-unit activity in patients during wakefulness and light anesthe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 85 publications
6
28
0
Order By: Relevance
“…In AC, comparable early responses in natural sleep observed here are in line with several recent reports (Peña et al, 1999;Edeline et al, 2001;Issa and Wang, 2008;Nir et al, 2015). In addition, a recent study comparing auditory responses at the neuronal level in humans across wakefulness and light anesthesia found a similar distinction between relatively preserved early responses in AC versus robust attenuation of late responses in association cortex (Krom et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In AC, comparable early responses in natural sleep observed here are in line with several recent reports (Peña et al, 1999;Edeline et al, 2001;Issa and Wang, 2008;Nir et al, 2015). In addition, a recent study comparing auditory responses at the neuronal level in humans across wakefulness and light anesthesia found a similar distinction between relatively preserved early responses in AC versus robust attenuation of late responses in association cortex (Krom et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a recent study comparing auditory responses at the neuronal level in humans across wakefulness and light anesthesia found a similar distinction between relatively preserved early responses in AC vs. robust attenuation of late responses in association cortex (Krom et al, 2018). What could be the source of apparent discrepancy with earlier studies in other sensory modalities that reported attenuated spiking responses in primary cortices during natural sleep?…”
Section: Discussionmentioning
confidence: 86%
“…While the current results indicate that LC activity robustly modulates SEA, it remains unclear to what extent this co-occurs with corresponding response modulations along sensory pathways. While LC-NE signaling clearly modifies response fidelity across sensory modalities and species 49,94–96 , it is unlikely that it simply “gates” propagation of auditory signals to the cortex as auditory responses in primary cortex are largely comparable across vigilance states 9799 . Instead, tonic LC activity that drives SEAs may facilitate sensory processing downstream from primary regions, by acting at higher-order regions or non-sensory pathways to promote awakenings.…”
Section: Discussionmentioning
confidence: 99%